PENGGUNAAN MEDIA JARUM BERGOYANG DALAM MATERI MEDAN MAGNET UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK - BUDI HENDRATNO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of this paper is to further improve students' understanding of the concept of magnetic fields, by creating media that can show the characteristics of magnetic fields, which are abstract quantities and vector quantities. This media is designed in addition to being able to prove the existence of an abstract magnetic field, it can also show the direction of the magnetic lines of force, show the shape of the curved trajectory of the magnetic lines of force, and can directly determine the magnetic poles if the magnet is made by electromagnetic means. While the media that is often used so far can only prove its existence. The process of making this media through three stages, namely; design, assemble and test. This media is designed by using a needle that is placed above the water and brought close to a magnet with the media term